Perancangan dan Implementasi Sistem Operasi Linux Debian untuk Konfigurasi Content Management System (CMS) Wordpress Dengan Winscp - Basorudin; Gunarso; Erni Rouza; Luth Fimawahib; Asep Supriyanto (Bulletin of Computer Science Research, 2022)
The operating system is one of the vital components in a computer system. The operating system is responsible for managing the use of computer hardware such as processors, memory, I/O devices, storage media, and others.( Wamiliana, At All. 2013). The purpose of making this title is the first as a reference for future researchers in creating websites but using Linux and as a reference for lecturers and teachers especially in the field of computer networks for teaching and for making scientific work related to the same problem but using a different Linux, for example Ubuntu, Mandrake, Caldera and other operating systems. This research has been successfully carried out with the final result in the form of Debian Linux implementation for website creation. In making a Wordpress CMS Website using Linux, you don’t need internet access, but instead create your own server with a text-based Debian Linux operating system, and the result is a Graphic User Interface (GUI) display that can be accessed, modified, added images, added videos, changed background, installed. Plugin, post news like wordpress which is connected to the internet.